Halal Edu-Tourism: Discovering the Rich Culture of Lombok Through Education and Travel - Athar, Lalu Mohamad Iswadi (PINISI Discretion Review, 2025)
The growing demand for halal tourism that integrates cultural, spiritual, and educational experiences has positioned Lombok as a promising destination for the development of halal edu-tourism. This study aims to explore the potential of halal edu-tourism in Lombok by identifying key cultural, educational, and institutional factors that can support its development. A qualitative research approach was employed, using in-depth interviews, focus group discussions, and field observations involving stakeholders from the tourism sector, educational institutions, local communities, and policymakers. The collected data were analyzed thematically to capture recurring patterns, challenges, and opportunities related to the integration of education and halal tourism. The findings indicate that Lombok possesses strong cultural and Islamic heritage assets that are suitable for halal edu-tourism development; however, its implementation is constrained by limited coordination between the tourism and education sectors, insufficient educational program integration, and capacity gaps among local actors. Despite these challenges, there is a clear interest from stakeholders and a growing market demand for meaningful, learning-oriented halal travel experiences. Overall, the study concludes that halal edu-tourism in Lombok has considerable potential if supported by integrated strategies, stakeholder collaboration, and targeted capacity development to ensure sustainable and inclusive tourism growth.